Bagaimana Brand Love Memperkuat Peran Brand Ambassador dalam Mendorong Niat Beli Fashion Gen Z - Abdul Gofur; Hanuna Shafariah (Jurnal STEI Ekonomi, 2026)
This study investigates the interplay between Brand Love and Brand Ambassador in influencing the Purchase Intention of Generation Z consumers for global fashion products in Indonesia. Utilizing a quantitative survey design, data were collected from Generation Z consumers in Jakarta who had purchased products from major global fashion brands. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that Brand Ambassador significantly and positively affects Purchase Intention, establishing its direct role as a marketing stimulus. In contrast, Brand Love does not show a direct and significant influence on Purchase Intention when considered alongside the brand ambassador’s impact. Crucially, the analysis reveals that Brand Love acts as a significant moderator in the relationship between Brand Ambassador and Purchase Intention. The moderation effect confirms that Brand Love weakens this positive relationship. This suggests that for highly attached consumers, the influence of an external endorser becomes less pronounced. This research contributes to the Stimulus-Organism-Response (SOR) theory by positioning Brand Love as a contingency variable that affects the effectiveness of external stimuli on consumer behavior.